Preparation and Investigation of a Nanosized Piroxicam Containing Orodispersible Lyophilizate - Petra Party; Sándor Soma Sümegi; Rita Ambrus (Micromachines, 2024)
Non-steroidal anti-inflammatory piroxicam (PRX) is a poorly water-soluble drug that provides relief in different arthritides. Reducing the particle size of PRX increases its bioavailability. For pediatric, geriatric, and dysphagic patients, oral dispersible systems ease administration. Moreover, fast disintegration followed by drug release and absorption through the oral mucosa can induce rapid systemic effects. We aimed to produce an orodispersible lyophilizate (OL) consisting of nanosized PRX. PRX was solved in ethyl acetate and then sonicated into a poloxamer-188 solution to perform spray-ultrasound-assisted solvent diffusion-based nanoprecipitation. The solid form was formulated via freeze drying in blister sockets. Mannitol and sodium alginate were applied as excipients. Dynamic light scattering (DLS) and nanoparticle tracking analysis (NTA) were used to determine the particle size. The morphology was characterized by scanning electron microscopy (SEM). To establish the crystallinity, X-ray powder diffraction (XRPD) and differential scanning calorimetry (DSC) were used. A disintegration and in vitro dissolution test were performed. DLS and NTA presented a nanosized PRX diameter. The SEM pictures showed a porous structure. PRX became amorphous according to the XRPD and DSC curves. The disintegration time was less than 1 min and the dissolution profile improved. The final product was an innovative anti-inflammatory drug delivery system.